2017
DOI: 10.1016/j.smim.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota dysbiosis in select human cancers: Evidence of association and causality

Abstract: The human microbiota is a complex ecosystem of diverse microorganisms consisting of bacteria, viruses, and fungi residing predominantly in epidermal and mucosal habitats across the body, such as skin, oral cavity, lung, intestine and vagina. These symbiotic communities in health, or dysbiotic communities in disease, display tremendous interaction with the local environment and systemic responses, playing a critical role in the host’s nutrition, immunity, metabolism and diseases including cancers. While the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 109 publications
(164 reference statements)
3
111
0
3
Order By: Relevance
“…These findings are interesting since biofilms have also been associated with periodontal disease and F. nucleatum and Porphyromonas spp. are associated with both oral biofilms and colon cancer (4,11,25,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are interesting since biofilms have also been associated with periodontal disease and F. nucleatum and Porphyromonas spp. are associated with both oral biofilms and colon cancer (4,11,25,30).…”
Section: Discussionmentioning
confidence: 99%
“…KEYWORDS colorectal cancer, transcriptomics, microRNAs, microbiota, biofilm, germfree N umerous 16S rRNA and shotgun metagenomic studies have demonstrated that colorectal cancer (CRC) patients have an altered intestinal microbiota compared to healthy controls (1,2). Colibactin-producing Escherichia coli, enterotoxigenic Bacteroides fragilis, and Fusobacterium nucleatum among others, are implicated in CRC pathogenesis due to their abilities to produce genotoxins and adhesins which promote proliferation and modulate immune responses in preclinical models (3,4). How these bacteria interact with the rest of the complex microbiota to influence CRC initiation and/or progression is still unclear.…”
mentioning
confidence: 99%
“…Abnormal variations in the intestinal microbiome is a key factor in the development of many metabolic diseases such as obesity, type-2 diabetes, and atherosclerosis (14). In addition, gut microbes play an important role in constipation, diarrhea, colitis, chronic gastritis, urinary tract infections, skin aging, acne, osteoporosis (15), allergic diseases (16), liver cirrhosis (17), depressive disorder (18), cardiovascular diseases (19), lung diseases (9), autoimmune diseases (20), central nervous system disorders (21), and cancers (22). Therefore, the effect of the intestinal microbiome on the body's immune system is not just limited to the intestinal tract but is spread across the entire body.…”
Section: Human Microbiomementioning
confidence: 99%
“…Recently, increased abundance of Fusobacterium nucleatum, Bacteroides fragilis, and Escherichia coli have been associated with human CRC [1][2][3] . These species are hypothesized to promote tumorigenesis and/or progression of CRC through up-regulation of oncogenes, modification of intestinal mucus, or damage to host DNA 2,4,5 . In addition to the mere presence or absence of putative carcinogenic bacteria in the gut, the spatial localization and physical interaction with host epithelial cells may be critically important.…”
Section: Introductionmentioning
confidence: 99%